Documentation of the Development of Various Visuomotor Responses in Typically Reared Kittens and Those Reared With Early Selected Visual Exposure by Use of a New Procedure - MacNeill, Katelyn; Myatt, Amber; Duffy, Kevin R.; Mitchell, Donald E. (Frontiers in Neuroscience, 2021)
A new procedure was used to study the development of gaze (responses to moving targets or laser spots in normal kitten, those that had been reared in total darkness to 6 weeks of age, and others that received a period of monocular deprivation (MD). Gaze responses were observed to all stimuli in normal kittens at between 25 – 30 days of age and striking responses occurred on the same day or the next. Despite slow acquisition of spatial vision in the dark reared kittens over 3 months, they were able to follow and even strike at moving visual stimuli within a day of their initial exposure to light. By contrast, for a week following a period of MD, kittens showed no gaze or striking responses to moving stimuli when using their previously deprived eye. The very different profiles of acquisition of visuomotor skills and spatial vision in visually deprived kittens point to a dissociation between the neuronal populations that support these functions.